Emerging Market Business Cycles: The Cycle Is the Trend - Aguiar, Mark; Gopinath, Gita (Journal of Political Economy, 2007)
Emerging market business cycles exhibit strongly countercyclical current accounts, consumption volatility that exceeds income volatility, and â€œsudden stopsâ€ in capital inflows. These features contrast with developed small open economies. Nevertheless, we show that a standard model characterizes both types of markets. Motivated by the frequent policy regime switches observed in emerging markets, our premise is that these economies are subject to substantial volatility in trend growth. Our methodology exploits the information in consumption and net exports to identify the persistence of productivity. We find that shocks to trend growthâ€”rather than transitory fluctuations around a stable trendâ€”are the primary source of fluctuations in emerging markets. The key features of emerging market business cycles are then shown to be consistent with this underlying income process in an otherwise standard equilibrium model.